Optimization and validation of a high performance liquid chromatography method for the simultaneous determination of vitamins A and E in human serum using monolithic column and diode-array detection - Urbánek, Lubor; Solichová, Dagmar; Melichar, Bohuslav; Dvořák, Josef; Svobodová, Iveta; Solich, Petr (Analytica chimica acta, 2006)
In this study a novel, simple and rapid reversed-phase high performance liquid chromatography (HPLC) procedure for simultaneous determination of vitamins A and E (retinol and alpha-tocopherol) in blood serum has been developed and validated using monolithic column and diode-array detection (DAD). The monolithic column Chromolith Performance RP-18e (100 mm x 4.6 mm) was operated at ambient temperature. One hundred percent methanol at flow rate 2.5 ml min(-1) was used as a mobile phase. Detection of both compounds was performed with diode-array detector, retinol was monitored at 325 nm and alpha-tocopherol at 295 nm. The linear dependence between peak area and concentration ranged from 0.25 to 10.00 micromol l(-1) for retinol and 0.5-50.0 micromol l(-1) for alpha-tocopherol. The limit of detection (LOD) for retinol was 0.02 micromol l(-1) and limit of quantification (LOQ) was 0.07 micromol l(-1). The limit of detection (LOD) for alpha-tocopherol was 0.1 micromol l(-1) and limit of quantification (LOQ) was 0.3 micromol l(-1). Retinol was eluted in 0.8 min and alpha-tocopherol in 1.4 min. The simultaneous analysis of vitamin A and E can be achieved in less than 2 min. The implementation of monolithic column Chromolith Performance shortens the time of analysis of both vitamins four times in comparison with using traditional particulate column Pecosphere C18 (150 mm x 4.6 mm), 5 microm. This fact may play an important role for routine clinical analysis of biological samples
Keywords: Serum; Vitamin A; alpha-Tocopherol; alfa-tokoferol; Chromatography, Liquid; vitamin A; chromatografie kapalinová; vitamin E; sérum; Vitamin E